P293 Influence of initial albumin levels on infliximab and adalimumab trough levels in inflammatory bowel disease patients. (16th January 2018) - Gonzalez-Lopez, J; Llamas, C; Giráldez-Montero, J M; Ferreiro, R; Baston, I; Lamas, M J; Dominguez-Munoz, J E; Barreiro-de Acosta, M
Abstract: Background: It has been shown that low albumin levels have been associated with poorer response to anti-TNF drugs. We hypothesise that albumin concentration at the start of treatment could influence infliximab (IFX) and adalimumab (ADA) trough levels. The aim of the study was to assess the influence of albumin levels on IFX and ADA concentrations. Methods: A retrospective study was carried out. Inclusion criteria were IBD patients treated with IFX or ADA who give consent to participate in the study. Exclusion criteria were those patients with presence of antidrug antibodies. Patients were included consecutively when visiting the Hospital to receive IFX/ADA. Blood samples were extracted for drug concentration determination. Albumin at the beginning of anti-TNF treatment (not at the time of sample extraction as in other studies) was registered, as well as body weight, gender and type of IBD. To avoid the influence of different dosing schedules, only patients under maintenance treatment with IFX 5 mg/kg every 8 weeks and ADA 40 mg every 2 weeks were selected. Chi square test was used to analyse categorical variables and t-student test to analyse continuous variables with normal distribution. Results: 76 patients were consecutively included, 30 (39%) men. Fifty-five (72%) Crohn's disease (CD) and 21 (28%) ulcerative colitis (UC), 46 (60%) had maintenance treatment with IFX and 30 (40%) with ADA. Mean weight was 68 kg. Initial mean albumin was similar (4.0 vs. 4.1 g/dl) in male and female groups. ADA trough levels were affected more than IFX trough levels by initial albumin values. When albumin is below 4 g/dl, ADA concentrations were lower (7.0 vs. 8.8 μg/ml ( p = 0.06), with 24.7% increase when albumin was >4 g/dl. In IFX the influence of albumin was very small (3.3 vs. 3.6 μg/ml with an increase of 8.9% when albumin >4 g/dl) Body weight affected drug ADA and IFX differently. In IFX it had no influence, but below 80 kg, ADA concentrations remained constant (8.9 μg/ml). However in>80 Kg patients, concentrations dropped to 6.7 μg/ml. In relation to gender, mean drug concentrations were 3.6/3.5 μg/ml (male/female) in IFX group and 7.5/9.0 μg/ml in ADA group ( p = 0.08). No significant changes in drug concentrations were observed between the CD and UC groups (9.05 vs. 8.31 μg/ml, 3.42 vs. 3.64 μg/ml, ADA and IFX respectively). Conclusions: Albumin concentrations had no significant influence on drug concentrations. Neither gender nor weight were significant. The results found allow us to rule out these factors as important sources of variability in drug concentrations.